(untitled) (Dhaka University Journal of Biological Sciences, 2020)
One of the major problems associated with rice cultivation and production is the deficiency of water resources. In here the effect of drought stress on growth, protein-, proline-, pigment contents and antioxidant enzymes activities in rice var. BRRI Dhan-24 was determined and analyzed under drought and wellwatered condition. Drought stress caused the decrease of growth and pigment contents - chlorophyll-a, b, a/b, total chlorophyll and carotenoids content of leaves of rice plants. On the other hand, the accumulation of protein, proline contents and antioxidant enzymes activities was increased under drought stress. It may be suggested that antioxidant enzymes activities and proline accumulation were associated with the growth of the plant and consequently with the mechanisms of drought tolerance in rice. Dhaka Univ. J. Biol. Sci. 29(1): 117-123, 2020 (January)